2018
DOI: 10.1590/1984-70332018v18n4a53
|View full text |Cite
|
Sign up to set email alerts
|

Yellow passion fruit reaction to Xanthomonas axonopodis pv. passiflorae and to Cowpea aphid-borne mosaic virus

Abstract: Yellow passion fruit (Passiflora edulis Sims) yield and longevity have been drastically reduced by bacterial spot (Xanthomonas axonopodis pv. passiflorae -Xap) and passion fruit woodiness disease (PWD) (Cowpea aphid-borne mosaic virus -CABMV). This study was aimed at evaluating the reaction of 11 genotypes of yellow passion fruit, based on the reaction of their progenies, to both mechanically inoculated Xap and CABMV, under greenhouse conditions. There was a progressive increase in bacterial spot and PWD sever… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
21
2
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
4

Relationship

4
0

Authors

Journals

citations
Cited by 4 publications
(26 citation statements)
references
References 20 publications
2
21
2
1
Order By: Relevance
“…MAR20#10 (37.5%) and MAR20#41 (25.0%) were the genotypes with the greatest numbers of resistant plants at the end of the study, contrasting with MAR20#19 (12.5%) and MAR20#2005 (5.9%). Differently from our findings, Costa et al (2018) did not observed a single resistant plant to Xap strain UnB-1393 after five evaluations in a distinct season. According to Fuhrmann et al (2014), these results point to the existence of diverse genetic resistance levels to bacterial spot, including within plants of the same genotype.…”
Section: Resultscontrasting
confidence: 99%
See 3 more Smart Citations
“…MAR20#10 (37.5%) and MAR20#41 (25.0%) were the genotypes with the greatest numbers of resistant plants at the end of the study, contrasting with MAR20#19 (12.5%) and MAR20#2005 (5.9%). Differently from our findings, Costa et al (2018) did not observed a single resistant plant to Xap strain UnB-1393 after five evaluations in a distinct season. According to Fuhrmann et al (2014), these results point to the existence of diverse genetic resistance levels to bacterial spot, including within plants of the same genotype.…”
Section: Resultscontrasting
confidence: 99%
“…The remaining genotypes were classified as MS (Table 2). Our findings are corroborated by Costa et al (2018) who also verified that MAR20#2005 (S) and MSCA (S) presented higher severity scores as compared to other genotypes when inoculated with UnB-1393 Xap strain during the wet season. Conversely, Nogueira (2016) found greater susceptibility of Rosa Intenso (MS), MAR20#41 (S), and MSCA (S) when 90-day-old plants were inoculated with UnB-1393 Xap strain during the same study period of this report.…”
Section: Resultssupporting
confidence: 86%
See 2 more Smart Citations
“…Naturally occurring multiple resistance to numerous pathogens have been recorded for a few crops (Melo et al, 2008;Neder, Pinto, Melo, Lepre, & Peixouto, 2010;Wisser et al, 2011). However, multiple pathogen reaction studies are limited for sour passion fruit (Costa et al, 2018a(Costa et al, , 2018b. Most studies performed for this crop under protected cultivation are focused on mechanical inoculation of a single pathogen (Fuhrmann et al, 2014;Viana et al, 2014aViana et al, , 2014b.…”
Section: Introductionmentioning
confidence: 99%